Matthew : all authority in heaven and on earth - O'Donnell, Douglas Sean, 1972-; Hughes, R. Kent, 1942- (Wheaton, Illinois : Crossway, 2013)
Jesus is King. Standing as a central theme of the Gospel of Matthew, Jesus kingly authority has profound implications for our lives todaychanging the way we view the world, interact with others, and respond to blessings and hardships. In this reader-friendly commentary, seasoned pastor Doug ODonnell leads us through the first book of the New Testament, highlighting key themes and offering contemporary illustrations for preaching. Drawing on years of pastoral experience, ODonnell helps us to see how Matthews various emphasesincluding Jesus messianic titles, fulfillment of Old Testament prophecy, teaching on the kingdom of heaven, and present and future role as judgeall relate to Christ's kingship over all of creation. Full of biblical insights aimed at both pastors and laypeople, this volume ultimately highlights Matthews call to all people to worship and obey Jesus, our humble King and gracious Savior
Includes index
Includes bibliographical references and index
Keywords: Bible. -- Commentaries; Bible. -- Homiletical use